FAITH-BASED APPROACHES OF WASTE MANAGEMENT:: A Case Study of Religious Enviromentalism in Indonesia - Ginting, Eikel (Religi: Jurnal Studi Agama-agama, 2025)
This paper explores the transformative role of religion in promoting sustainable waste management through case studies of faith-based communities in Indonesia. Despite being one of the most religious countries in the world, Indonesia still struggles with low levels of ecological awareness—particularly in household waste management. This paradox highlights the untapped potential of religion in cultivating environmental consciousness and driving behavioral change at the grassroots level. Utilizing a qualitative approach through a comprehensive literature review and case study analysis, the study investigates how religious values can be meaningfully integrated into environmental action. Three representative cases are examined: the Eco-Mosque initiative and At Thoriq Ecological Islamic Boarding School (Islam), the Waste Bank program by the Batak Karo Protestant Church (Christianity), and traditional waste practices in Penglipuran Village (Balinese Hinduism). The analysis reveals that teachings such as khalifah, stewardship, simplicity spirituality (ugahari), ahimsa (non-violence), and indigenous wisdom hold significant potential for fostering eco-friendly behaviors. However, the dominance of anthropocentric theological paradigms and limited structural policy support remain major challenges. The study argues that integrating spiritual values with waste management strategies requires cross-sector collaboration, including the reinterpretation of religious teachings, faith-based environmental education, and policy incentives for religious institutions. Ultimately, this paper affirms that religion is not only a source of personal spirituality but also a powerful force for collective ecological action—one that can inspire a greener, more sustainable future. Keyword: Eco-Theology, Waste Management, Faith-Based Environmentalism, Environmental Ethics,  Interfaith Initiatives   Tulisan ini mengkaji peran transformatif agama dalam mendorong pengelolaan sampah yang berkelanjutan melalui studi kasus pada komunitas-komunitas berbasis iman di Indonesia. Meskipun Indonesia dikenal sebagai salah satu negara paling religius di dunia, tingkat kesadaran ekologis masyarakat—khususnya dalam pengelolaan sampah rumah tangga—masih tergolong rendah. Paradoks ini menunjukkan adanya potensi besar yang belum dimanfaatkan dari ajaran agama dalam menumbuhkan kesadaran lingkungan dan mendorong perubahan perilaku di tingkat akar rumput. Dengan menggunakan pendekatan kualitatif melalui tinjauan pustaka yang komprehensif dan analisis studi kasus, penelitian ini menyelidiki bagaimana nilai-nilai keagamaan dapat diintegrasikan secara bermakna ke dalam aksi lingkungan. Tiga kasus representatif yang dianalisis meliputi: inisiatif Eco-Masjid dan Pesantren Ekologi At Thoriq (Islam), program Bank Sampah oleh Gereja Batak Karo Protestan (Kristen), serta praktik pengelolaan sampah berbasis adat di Desa Penglipuran (Hindu-Bali). Hasil analisis menunjukkan bahwa ajaran-ajaran seperti khalifah, penatalayanan, spiritualitas ugahari (kesederhanaan), ahimsa (tanpa kekerasan), dan kearifan lokal memiliki potensi signifikan dalam membentuk perilaku ramah lingkungan. Namun demikian, tantangan utama masih dihadapi, antara lain dominasi paradigma teologis yang bersifat antroposentris dan keterbatasan dukungan struktural dari kebijakan publik. Studi ini berargumen bahwa integrasi nilai-nilai spiritual dengan strategi pengelolaan sampah memerlukan kolaborasi lintas sektor, termasuk reinterpretasi ajaran keagamaan, pendidikan lingkungan berbasis iman, serta insentif kebijakan bagi institusi keagamaan. Pada akhirnya, tulisan ini menegaskan bahwa agama bukan hanya sumber spiritualitas personal, melainkan juga kekuatan kolektif yang mampu menginspirasi aksi ekologis demi masa depan yang lebih hijau dan berkelanjutan. Kata Kunci: Ekoteologi, Pengelolaan Sampah, Gerakan Lingkungan Berbasis Iman, Etika Lingkungan, Inisiatif Lintas Iman